The effectiveness of extension services provided by OPIC for the production of oil palm to smallholder growers in Hoskins, West New Britain Province - Mendano, Senny Kapia (Curtin University, 2012)
In Papua New Guinea, oil palm is regarded as a crop with great economic importance and is now the dominant export cash crop in terms of export revenue. It is grown in six provinces in PNG which are Hoskins and Bialla in West New Britain Province, Popondetta in Oro Province, Higaturu in Milne Bay Province, Poliamba in New Ireland Province and Ramu in Madang Province. The study examined the effectiveness of OPIC extension services provided to smallholder oil palm growers in Hoskins. The research included growers in the Hoskins land settlement scheme (LSS) and village oil palm (VOP) growers in the Hoskins project area. The LSS subdivision studied was Buvussi and the VOP subdivisions were Bubu and Lilimo. The main purpose of the study was to identify the factors hindering smallholders’ productivity on oil palm as their production (tonnes per hectare) was considerably below the estate plantations managed by the company. To investigate smallholder production, factors such as smallholder block population, education levels of grower families, leaseholder status, type of production strategy, adoption rate of extension messages and productivity were investigated. The study used both qualitative and quantitative methods to investigate these aspects of smallholder production and extension.The findings of the study indicate that there was low extension contact between the extension officers and smallholders with most visits because of sexava infestations. The low ratio of extension officers to blockholders was a factor in limiting OPIC (the extension agency) capacity for block visits. The majority of blockholders received their extension information through their visits to the OPIC office. However, the study revealed that the majority of blockholders were knowledgeable about oil palm and had excellent management skills on oil palm production. The study revealed that the education level of children in secondary households was adversely affected as priority was given to children in primary households.Due to population and income pressures, the single household block has been replaced with multiple household blocks and this has led to changes in the production strategies pursued on blocks. The harvesting strategy has shifted from the traditional harvesting method (wok bung) to makim mun, skelim hecta and some blocks practising a mixture of all three strategies. However, wok bung was found to be the most productive method of harvesting in terms of tonnes/ha/year. The study also found that population and income pressures have influenced blockholders’ decision-making process to adopt extension messages on fertilizer and replanting, thus there was low adoption levels. The low level of fertilizer application was due to increases in fertilizer prices over the last five years and also was due to disputes over block management which has led to falling productivity. The makim mun strategy of harvesting was also found to have an influence on adoption. However, reluctance to replant was because most blockholders were ferarful of debt accumulation and financial constraints due to loss of income after replanting.Therefore, the study recognised that smallholders’ low production was not due to lack of knowledge and skills on oil palm but was due to stresses associated with rising population pressures, together with the ineffectiveness of extension services provided by OPIC to smallholders.